A Case of Pneumococcal Peritonitis after Caesarean Section in a Healthy Woman. (13th October 2015) - Kourounis, Georgios; Panayiotou, Yiannis; Tabet, Patrick Paul; Richards, Brian David Wensley; Petrou, Athanasios; Loizou, Marios
Abstract : Pneumococcal peritonitis is prevalent in children and adults with comorbidities but extremely rare in healthy adults. Here we describe a case of pneumococcal peritonitis in a previously healthy woman with no known risk factors who presented with constipation, abdominal pain, and distention. Her only past medical history was an uncomplicated C-section two months prior to presentation. A laparotomy revealed a pneumococcal peritonitis without visible source of infection. The patient remained hospitalized until completion of antibiotic regimen with Ceftriaxone and resolution of symptoms. This report adds to the small body of evidence showing possible pneumococcal peritonitis in healthy young adults.